‘VIPS’ of knowledge / Mohammad Izuddin Jaal and Muhamad Izzat Mohd Yusoff - Jaal, Mohammad Izuddin; Mohd Yusoff, Muhamad Izzat (Faculty of Information Management, 2015)
The process of distribution and creation of knowledge, there are people whom involved throughout this process. The earlier findings of certain knowledge in certain subjects, for instance sciences, technologies, philosophy and even psychology, there are name behind all these fields. In this article, authors highlighted 4 great names and names them as knowledge 'VIPs' on their own findings which are people whom give a lot of contribution and having themselves with a lot of wisdoms to be shared among societies. The names highlighted are Ibn Sina, Tun Dr. Mahathir Mohamed, John Dewey and Elbert Einstein. Because of their big involvement in sharing knowledge with others, the story of their life must be something interesting to be shared so, authors decided to explain on 3 main subtopics which are the brief biography, the foundation or contribution, and the creation of knowledge of these 'VIPs'.